The Social Class in 1984 - Andika Aliyansah Putra (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
Abstract This study analyzes the depiction of social class in George Orwell's 1984 novel. The discussion will focus on how the depiction of social class and social class as a trigger for rebellion by Winston Smith as the main character in the novel. Winston Smith as a party member who works for Big Brother wants to rebel secretly. Winston is not alone; he meets Julia who has the same desire as Winston. Referring to the problem, this thesis explains two problems about: (1) The depiction of social class in the 1984 novel and (2) Social class triggers Winston's rebellion. This article uses the supporting theory of Marxism by Karl Marx and rebellion Key words: Rebellion, Marxism by Karl Marx, social class